The “Colong” Marriage Tradition in Osing Society: A Legal-Anthropological Analysis of Islamic Religious Texts and Cultural Practices in Banyuwangi - Achmad Sofiyul Mubarok; Mohammad Ainun Rofiq; M Khoirul Hadi al-Asyari (Journal of Feminism and Gender Studies, 2026)
Colong marriage in the Osing community in Banyuwangi is a unique cultural practice, in which couples marry secretly without the direct consent of the bride's parents. This practice is often considered to violate customary norms and Islamic law, particularly regarding the validity of marriage contracts and the role of marriage guardians. However, this phenomenon persists and remains socially accepted in certain contexts. This study aims to answer the question: How is the practice of colong marriage understood and negotiated by the Osing community within the framework of Islamic law and local traditions? This research fills the research gap in the lack of studies that link this local practice with analysis of classical Islamic religious texts and legal anthropology approaches. The method used is a qualitative study based on literature. Research with a legal anthropology approach. Data were obtained from classical and contemporary Islamic legal literature, ethnographic documents, and previous studies on the Osing community. The theories used are legal pluralism and power relations in legal anthropology. The results of this study indicate that the practice of colong is not merely a form of defiance, but rather a social and cultural strategy to respond to the imbalance of parental authority, social control over women, and the dynamics of interpretation of Islamic law at the local level. This indicates a shift in religious and cultural authority relevant to the discourse of Islamic legal feminism.